2010
DOI: 10.1186/cc9395
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid lactate concentration to distinguish bacterial from aseptic meningitis: a systemic review and meta-analysis

Abstract: IntroductionMaking a differential diagnosis between bacterial meningitis and aseptic meningitis is a critical clinical problem. The utility of a cerebrospinal fluid (CSF) lactate assay for this purpose has been debated and is not yet routinely clinically performed. To adequately evaluate this assay, a systematic review and meta-analysis of studies of the CSF lactate concentration as a marker for both bacterial meningitis and aseptic meningitis was performed.MethodsElectronic searches in PubMed, Scopus, the MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(108 citation statements)
references
References 58 publications
5
87
2
10
Order By: Relevance
“…CSF lactate concentration may differentiate bacterial from viral meningitis better than white blood cell count, glucose level, and protein concentration, although CSF lactate may be elevated in patients with other CNS diseases. 42,43 The level of protein can be elevated in many infectious and noninfectious diseases as well as in traumatic lumbar puncture and subarachnoid bleeding. Creatinine kinase and lactate dehydrogenase (LDH) CSF levels are also high in pyogenic or tubercular meningitis.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…CSF lactate concentration may differentiate bacterial from viral meningitis better than white blood cell count, glucose level, and protein concentration, although CSF lactate may be elevated in patients with other CNS diseases. 42,43 The level of protein can be elevated in many infectious and noninfectious diseases as well as in traumatic lumbar puncture and subarachnoid bleeding. Creatinine kinase and lactate dehydrogenase (LDH) CSF levels are also high in pyogenic or tubercular meningitis.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Otherwise, the fixed-effects model (MantelHaenszel) (Higgins and Thompson, 2002) was used. Further, Galbraith plot analyses were used to visualize the impact of individual studies on the overall homogeneity, which identified the outlier as possible major sources of heterogeneity (Huy et al, 2010). Sensitivity analyses were conducted to evaluate the stability of the combined results by omitting one study at a time or excluding those studies that deviated from HWE (Yang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, serum procalcitonin (PCT) and CSF lactate have the most potential to be useful clinically, with performances that are similar to or better than conventional CSF parameters in research studies (34,35). However, both biomarkers are nonspecific and can be affected by prior antibiotic treatment and noninfectious conditions, making it unclear how generalizable these results are to routine clinical practice.…”
Section: Current Diagnostic Test Methodsmentioning
confidence: 99%